2017
DOI: 10.1162/jocn_a_01164
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Exercise and Cognitive Training on Memory and Neurotrophic Factors

Abstract: This study examined the combined effect of physical exercise and cognitive training on memory and neurotrophic factors in healthy, young adults. Ninety-five participants completed 6 weeks of exercise training, combined exercise and cognitive training, or no training (control). Both the exercise and combined training groups improved performance on a high-interference memory task, whereas the control group did not. In contrast, neither training group improved on general recognition performance, suggesting that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 109 publications
4
83
2
3
Order By: Relevance
“…; Heisz et al. ). Handedness was determined using a modified Edinburgh inventory questionnaire, which provides a laterality quotient (LQ) (Oldfield ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Heisz et al. ). Handedness was determined using a modified Edinburgh inventory questionnaire, which provides a laterality quotient (LQ) (Oldfield ).…”
Section: Methodsmentioning
confidence: 97%
“…Lastly, Heisz et al. () reported that, although no group differences in serum BDNF were found following 6 weeks of high‐intensity interval training in young adults, participants with greater fitness improvements had higher serum BDNF levels than their counterparts with lower fitness gains. One of the goals of the present study was to investigate whether serum BDNF was enhanced after 6 weeks of high‐intensity interval training in sedentary males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasticity mechanism may be through exercise-induced release of neurotrophins (McDonnell et al, 2013). For the purpose of this review we have decided to focus on two neurotrophins, vascular endothelial growth factor (VEGF) and brain-derived neurotrophic factor (BDNF), both of which have been shown to be upregulated after various types of physical exercise (Maass et al, 2016;Heisz et al, 2017).…”
Section: Plasticity and Neurotrophic Factorsmentioning
confidence: 99%
“…Given this situation, the literature has proposed several therapies to delay changes related to the loss of cognitive function in the elderly. Among these, physical exercise is a low cost and effective non-pharmacological alternative for memory prevention / rehabilitation, acting positively on cerebral angiogenesis, neurogenesis, and synaptogenesis [7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%